Role of Religious Rituals in Shaping Mental Health Coping Mechanisms among Different Cultural Groups in Japan - Suzuki, Hana (International Journal of Culture and Religious Studies, 2025)
Purpose: The purpose of this article was to analyze role of religious rituals in shaping mental health coping mechanisms among different cultural groups in Japan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Religious rituals in Japan, like Shinto and Buddhist practices, help shape mental health coping mechanisms. Rituals such as prayer, meditation, and shrine visits provide emotional support, foster resilience, and promote mindfulness. These practices offer a sense of community and meaning, helping to reduce stress and improve well-being, though their impact varies across cultural groups based on religious participation. Unique Contribution to Theory, Practice and Policy: The cognitive behavioral Theory (CBT), the social support theory & the meaning-making theory may be used to anchor future studies on the effect of cultural festivals on the preservation of religious traditions in immigrant communities in Nigeria. By offering teachings on the religious significance of the rituals performed, younger generations can be better equipped to understand and engage with their cultural and religious heritage. Policymakers should consider providing financial support for cultural festivals that play a significant role in the preservation of religious traditions.